Effect of Ethanol-water Concentration as Extraction Solvent on Antioxidant Activity of Acalypha indica - Salma Iza Fadhila; Elok Kamilah Hayati; Mohamad Rafi; Akhmad Sabarudin (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Acalypha indica is an abundant and obtainable wild weed plant in Indonesia. This is a possible opportunity to enhance its utility. The effect of free radicals is one of the factors that contribute to oxidative stress in the body, which can lead to cell damage and trigger various diseases. Plants rich in antioxidants can inhibit free radical reactions and protect the body from oxidative stress. In this study, we conducted the identification of major metabolite compounds using UHPLC-Q-Orbitrap HRMS from 70% ethanol extracts of Acalypha indica. We also performed phytochemical and antioxidant activity tests with various concentrations of ethanol-water solvents including water, 30%, 50%, 70% ethanol, and absolute ethanol to determine the optimal extraction conditions and the influence of solvent concentration on the antioxidant activity of Acalypha indica extract. The results of UHPLC-Q-Orbitrap HRMS identification showed that the 70% ethanol extract of Acalypha indica contains 10 major compounds suspected to correlate with its antioxidant activity. These include five flavonoids compounds (palasitrin, vitexin 2